On Indexes for Analysis of Main Engine Real Load at Sea - Liu, QianShan; Hashimoto, Jun; Uchida, Makoto (JOURNAL OF THE MARINE ENGINEERING SOCIETY IN JAPAN, 1986)
It is very important for shipping to grasp the service performance of ships. But the analysis of ablogbook, the main information source, is not easy. Based on the understanding, that separate from the propeller characteristics, the load condition of whole main engine+propeller+hull system can not be analysed, it is shown that the time series of indexes, which can be seen as mimetic propeller characteristics, is useful for the analysis of main engine real load.